C‐perpendicular orientation in thin nanoporous‐crystalline poly(2, 6‐dimethyl‐1, 4‐phenylene)oxide films. (16th April 2022) - Nagendra, Baku; Daniel, Christophe; Rizzo, Paola; Guerra, Gaetano
Abstract: Nanoporous‐crystalline films of poly(2, 6‐dimethyl‐1, 4‐phenylene)oxide (PPO), exhibiting c‐perpendicular orientation (c ⊥ ) orientation (i.e., the orientation of the crystalline chain axes being preferentially perpendicular to the film plane), show the advantage of faster guest diffusivity and higher transparency. However, by using the methods described in the literature, this perpendicular orientation cannot be achieved for low thickness films (≤20 μm). In this paper, we describe four different preparation methods, which are suitable to get high degree of crystallinity ( X c  >40%) as well as high degree of c ⊥ orientation (−0.5<  f c  <− 0.3) of CC and NC α forms, for film thickness even as low as 5 μm. All the described methods are based on reduction of guest sorption kinetics. The reported results also confirm our previous hypothesis that c ⊥ orientation is due to formation of flat‐on crystalline lamellae, which in turn are due to nanoconfined co‐crystallization of PPO. An anomalous temperature dependence of c ⊥ orientation for limonene‐induced co‐crystallization with PPO is described and rationalized.